Penerapan Media Pembelajaran Bahasa Inggris Berbasis Kearifan Lokal dan Teknologi (ICT) di Sekolah Menengah Atas - Ibrahim, Muliaty; Jamal, Munarti (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program implemented locally wisdom–based English learning media to enhance the communicative competence of senior high school students. The program aimed to (1) design and produce culturally grounded learning media, (2) strengthen teachers’ capacity to apply communicative tasks using the media, and (3) observe changes in students’ classroom interaction and speaking performance. The program was conducted at [Partner Senior High School], involving 35 students and English teachers as co-implementers. The service stages included needs assessment, collaborative media development, teacher mentoring, classroom implementation, and evaluation. Learning media integrated local wisdom content—such as local legends, historical sites, symbols, and everyday community practices—into communicative activities (role play, information-gap, storytelling, guided tours, and problem-solving tasks). Evaluation used classroom observations, teacher reflection logs, student questionnaires, and speaking performance tasks assessed with a communicative competence rubric (fluency, vocabulary, grammatical control, intelligibility, and interaction strategies). Findings indicate that culturally relevant media increased students’ willingness to communicate, improved peer interaction during tasks, and supported more meaningful speaking practice. The program suggests that local wisdom–based media can serve as authentic communicative prompts and identity-affirming content, especially when accompanied by structured teacher mentoring for sustainable implementation.